Rasulullah Sebagai Guru dan Pendidik Ideal Manusia [Kajian Sosiologis] - Hanina Maria Ulfa (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This study explores the role of the Prophet Muhammad as an ideal teacher and educator in Islamic education, which is relevant to the challenges of today's education. A sociological approach is used to analyze his contribution in shaping the norms and culture of society. This study uses a qualitative method with a descriptive-analytical approach. Data were collected from primary sources such as the Qur'an and Hadith and secondary references in the form of scientific literature related to Islamic education and the history of the Prophet Muhammad. The results of the study show that the Prophet Muhammad not only taught science, but also instilled spiritual, social, and moral values. He practiced effective teaching methods such as a dialogical approach and direct role models. In addition, the Prophet Muhammad succeeded in creating significant social change, including upholding social justice, promoting equal rights, and eliminating discrimination. The education taught by the Prophet Muhammad was holistic, covering intellectual, spiritual, and social aspects. His teachings are relevant to modern education, especially in forming people with noble character and able to face global challenges. The Prophet Muhammad was an ideal educator figure who was not only relevant in his time, but also an inspiration for today's education. Implementation of the educational values ​​of the Prophet Muhammad can build an intelligent generation with noble morals and social justice.